AN ANALYSIS OF USING YOUTUBE VIDEOS IN TEACHING SPEAKING AT THE ELEVENTH GRADE LEVEL - Hulu, Tri Mulia Damai; Daeli, Hidayati; Laoli, Adieli; Waruwu, Yaredi (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
ABSTRACT This study aims to analyze the utilization of YouTube videos in English language learning and their impact on the development of students’ speaking skills amid the increasing use of digital media as learning resources. The integration of technology in language learning has become an important strategy to provide authentic materials and enhance students’ engagement in the learning process. This study employed a qualitative approach, with data collected through classroom observations, interviews with teachers and students, and analysis of instructional documents. The data were analyzed descriptively to obtain a comprehensive understanding of the practice of using YouTube videos in English language instruction. The findings indicate that the use of YouTube videos enhances students’ learning motivation and provides more authentic language exposure through examples of pronunciation, intonation, and expressions in real communication contexts. In addition, video-based learning creates greater opportunities for students to actively practice speaking through discussions, imitation activities, and content-based presentations. However, the study also identified several challenges, including limited internet access, variations in content quality, and potential distractions from other features on the digital platform. In synthesis, these findings confirm that YouTube videos are effective in supporting the development of speaking skills when they are integrated in a planned, selective, and pedagogically sound manner within English language teaching strategies. ABSTRAK Penelitian ini bertujuan untuk menganalisis pemanfaatan video YouTube dalam pembelajaran bahasa Inggris serta dampaknya terhadap pengembangan keterampilan berbicara siswa di tengah meningkatnya penggunaan media digital sebagai sumber belajar. Integrasi teknologi dalam pembelajaran bahasa menjadi strategi penting untuk menghadirkan materi yang autentik dan meningkatkan keterlibatan siswa dalam proses belajar. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui observasi pembelajaran, wawancara dengan guru dan siswa, serta analisis dokumen pembelajaran. Data dianalisis secara deskriptif untuk memperoleh gambaran komprehensif mengenai praktik penggunaan video YouTube dalam pembelajaran. Hasil penelitian menunjukkan bahwa pemanfaatan video YouTube meningkatkan motivasi belajar serta memberikan paparan bahasa yang lebih autentik melalui contoh pelafalan, intonasi, dan ekspresi dalam konteks komunikasi nyata. Selain itu, penggunaan video membuka peluang bagi siswa untuk berlatih berbicara secara aktif melalui diskusi, imitasi, dan presentasi berbasis konten. Namun, penelitian ini juga mengidentifikasi kendala berupa keterbatasan akses internet, variasi kualitas konten, dan potensi distraksi dari fitur lain pada platform digital. Secara sintesis, temuan ini menegaskan bahwa video YouTube efektif dalam mendukung pengembangan keterampilan berbicara apabila diintegrasikan secara terencana, selektif, dan pedagogis dalam strategi pembelajaran bahasa Inggris.